Research into a timetable forming tool for final classes (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
In this paper a high-school timetable forming tool is described. Commercial products and software for this problem solving are compared. The problems of timetable forming are analyzed. A decision for initial data computing is described. A new tool for computing problems solution is described. The results of this tool are analyzed.